Pengembangan Fitur Tampilan Status Dosen Berbasis Raspberry Pi dengan Metode Rapid Application Development (RAD) di Lingkungan Akademik - Hamdana, Elok Nur; Rizky Yunianto, Dika; Eka Apriyani, Meyti (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2025)
The advancement of information technology drives improvements in academic services, including providing fast and transparent access to lecturer attendance status information. This study develops a Raspberry Pi-based lecturer status display to show real-time lecturer attendance. The system is developed using the Rapid Application Development (RAD) method through the stages of data collection, analysis, design, implementation, and testing. Functional testing results show a 98% accuracy rate in data synchronization between the database and the display screen. A questionnaire distributed to 12 lecturers revealed that 86.7% of respondents found the application highly beneficial in quickly and transparently obtaining lecturer attendance information. Thus, this application can enhance efficiency and information transparency in the academic environment